The Study of Abundance of Soil Minerals on Micro Toposequen of Karst Gunungsewu Pegunungan Selatan - Mulyanto, Djoko (JOURNAL OF TROPICAL SOILS, 2008)
Landform of Gunungsewu karst topography dominated by positive forms consists of hills and negative forms of dolines. On the micro toposequen of karst,   most of dolines dominated by red soils which hue 2.5 YR – 5 YR, whereas on hills by soils which hue 5 YR – 7.5 YR. The aim of research was to study of soil minerals status on karst micro toposequent. Results showed that soil minerals of sand fraction on dolines dominated by quartz, opaque, and iron concretion, whereas on hills dominated by labradorite, and mafic minerals. Clay minerals on doline dominated by kaolinite whereas on hills by halloysite. The high concentration of kaolinite, quartz, opaque and iron concretions of soils on dolines appropriate with degree of  soil weathering  which in a line with decreasing of soil pH, silt/ clay ratio, and  hue of soils on dolines redder than hue of soils on hills.  The origin of soil parent material suggested come from volcanic materials.